The thesis work in the doctoral fomation process - Maricela María González Pérez; Tomás Castillo Estrella (Revista MENDIVE, 2020)
In the process of doctoral formation, the researching skills formation is essential, one of the ways that the doctoral committees can use to impact on it, are the thesis workshops, thus the objective of the present article is proposingactions to perform their fulfillment at their formative function refers. To accomplish with that objective, there were employed since the theoretical point of view, the historical-logical method and the systemic one and the technique of documental analysis, while at the empiric point of view, it was employed the measuring method and the techniques of documentary analysis, the questionnaire and the interview. As main results, there were identified since the theory, the skills to form, as well as the thesis workshops characteristics and since practicing, the difficulties of the workshops at the Pinar del Rio University, among there are: the insufficient visibility of the applicants publications, the little use of the info technological tools, the diversity of methodologies to improve the workshops at the different programs, the insufficient debate and plea by the applicants, among others, that´s why it concludes with a proposal to normalize the implementation of the workshops at the university to elevate their quality and impact.